Influência do biofeedback no treino de marcha de sujeitos hemiparéticos: ensaio clínico randomizado - Lima, Ana Carolina de Azevedo (2011)
BACKGROUND: Treadmill training with partial body weight support (BWS) has shown many benefits for patients after a stroke. But their findings are not well known when combined with biofeedback. OBJETIVE: The purpose of this study was to evaluate the immediate effects of biofeedback, visual and auditory, combined with treadmill training with BWS on on walking functions of hemiplegic subjects. METHODS: We conducted a clinical trial, randomized controlled trial with 30 subjects in the chronic stage of stroke, underwent treadmill training with BWS (control), combined with visual biofeedback, given by the monitor of the treadmill through the symbolic appearance of feet as the subject gave the step; or auditory biofeedback, using a metronome with a frequency of 115% of the cadence of the individual. The subjects were evaluated by kinematics, and the data obtained by the Motion Analysis System Qualisys. To assess differences between groups and within each group after training was applied to ANOVA 3 x 2 repeated measures. RESULTS: There were no statistical differences between groups in any variable spatio-temporal and angular motion, but within each group there was an increase in walking speed and stride length after the training. The group of visual biofeedback increased the stance period and reduced the swing period and reason of symmetry, and the group auditory biofeedback reduced the double stance period. The range of motion of the knee and ankle and the plantar flexion increased in the visual biofeedback group. CONCLUSION: There are no differences between the immediate effects of gait training on a treadmill with BWS performed with and without visual or auditory biofeedback. However, the visual biofeedback can promote changes in a larger number of variables spatiotemporal and angular gait